An optimization approach for panel dimension design in underground coal mines - Mallı, Tahir; Yetkin, Mustafa Emre (Kuwait Journal of Science, 2019)
Global energy demand increases the coal production in the last decades. Productive and cost-effective production and work safety are important factors in terms of underground coal mine design and planning. Generally, coal production is provided by longwall method to maximize production extracting large panel blocks in underground. Longwall method is designed by some technical parameters and constraints such as panel dimension, face and panel length. This study deals with determination of the optimum face length, panel length and their relations in mining planning. In this study, the ratio of panel length to face length (PL/FL) is derived in underground coal mining planning. If this rate lower, mining loss are also decreasing. In the proper panel dimension selection, the optimum zone is suggested to keep mining losses in optimum limits. This zone provides panel dimension planning within more efficient and safe place for longwall coal operations. Usually, PL/FL rate is lower in this zone. Therefore, the low rates of PL/FL will reduce coal mining losses. With reducing mining losses, the increased productivity will also provide to reduction of fixed cost. With this approach, it is foreseen that designing of coal panel can be realized for more efficient production.